2018
DOI: 10.1111/iwj.12875
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of using a new polyurethane foam multi‐layer dressing in the sacral area to prevent the onset of pressure ulcer in the elderly with hip fractures: A pragmatic randomised controlled trial

Abstract: Hip fractures in the elderly are a serious problem for the health service due to the high rate of complications. One of these complications is pressure ulcers that, according to the literature, occur in 8.8% to 55% of patients and mainly arise in the sacral area. The present randomised controlled trial tests whether applying a new innovative multi-layer polyurethane foam dressing (ALLEVYN LIFE™), reduces the onset of pressure ulcers in the sacral area. From March to December 2016, 359 fragility hip fracture pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
67
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 24 publications
(36 reference statements)
1
67
1
1
Order By: Relevance
“…The most common study design was RCTs ( n = 6). Regarding the PU preventive interventions, most of the featured studies focused on support surfaces, health professional's education, multiple intervention programmes, repositioning and early mobilisation, preventive skincare, prophylactic dressings, remind systems on patient care plan, and risk‐assessment tools . According to the care setting where the studies were carried out, most of them ( n = 17) were developed in intensive care units (ICU) followed by medicine ( n = 6), geriatrics ( n = 2), surgical ( n = 2), orthopaedics ( n = 2), oncology ( n = 1), rehabilitative ( n = 1), community hospital ( n = 1), and other specific units ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common study design was RCTs ( n = 6). Regarding the PU preventive interventions, most of the featured studies focused on support surfaces, health professional's education, multiple intervention programmes, repositioning and early mobilisation, preventive skincare, prophylactic dressings, remind systems on patient care plan, and risk‐assessment tools . According to the care setting where the studies were carried out, most of them ( n = 17) were developed in intensive care units (ICU) followed by medicine ( n = 6), geriatrics ( n = 2), surgical ( n = 2), orthopaedics ( n = 2), oncology ( n = 1), rehabilitative ( n = 1), community hospital ( n = 1), and other specific units ( n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…The study conducted by Dutra et al showed that polyurethane film dressings were more effective than hydrocolloid dressings in decreasing PU incidence in the trochanteric and sacral areas for patients cared for in the ICU, coronary unit, and in one general medicine unit . Other studies found that a multilayered silicone foam dressing was effective in reducing PUs on heels and sacrum in orthopaedics patients and patients in ICU when previously applied in emergency department or within 24 hours of admission to the ICU . Multilayered silicone foam dressing applied on sacrum in a special population like patients with spinal cord injury did not show a higher effectiveness in terms of PU prevention when compared with a gel mattress .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The principle underlying mode of action of the investigated dressings is lower friction between the outer dressing and the support surfaces, thus reducing shear within the skin and underlying soft tissues . Other types of dressings are used for PU prevention and study results are mixed . Therefore, compared with many other areas in PU prevention research, direct head‐to‐head comparisons are urgently needed to support clinical decision making …”
Section: Discussionmentioning
confidence: 99%